Zwierzę jako towarzysz ludzkiej doli i niedoli w twórczości Tadeusza Konwickiego - Łopata , Łukasz (Colloquia Litteraria, 2024)
The Vilnius region and its natural landscape are recurring themes in Tadeusz Konwicki’s works. In addition to the extensive descriptions of the world of flora, there are also animals which become full-fledged and integral literary characters. For this reason, the article aims to present a zoocritical reading of Konwicki’s texts, placing the pet as the primary object of research interests. Animals act as human companions, living together in a complex network of relationships. Based on the fragments of Konwicki’s writings, it is shown that the human- animal dichotomy can be replaced by mutual coexistence.